Aspek Kesehatan Lingkungan, Pengetahuan, dan Perilaku Warga dalam Menghadapi Pandemi COVID-19 - Ali, Shahrani Deviana; Pawenang, Eram Tunggul (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: Based on COVID-19 data in Semarang City as of July 15, 2021, there were 2,048 confirmed positive cases and 5 positive cases were found in Sekaran Village. The purpose of the study was to describe the environmental health factors, knowledge and behavior of residents in preparedness for the COVID-19 pandemic in Sekaran Village, Semarang City. Methods: The type of research is descriptive quantitative. The research subjects were 100 residents of Sekaran Village. The variables included spraying disinfectants, habit of washing hands with soap (WHWS), knowledge, use of masks, WHWS facilities, physical distancing and the habit of disposing of garbage. Instruments in the form of questionnaires and checklist sheets. The sampling technique used proportional random sampling. Data were analyzed using univariate test. Results: Results: Shows that the details of the level of community preparedness in facing a pandemic in the form of spraying disinfectants (20%), WHWS facilities (75%), knowledge (11%), use of masks (28%), WHWS habits (49%), physical distancing (64%), habit of throwing garbage (70%). Conclusion: The level of community preparedness is categorized as not ready, of 7 variables, there were 5 variables that were not ready, namely spraying disinfectants, knowledge, using masks, maintaining physical distance, and WHWS habits.